Community trade mark - Ergüven, Hayri (My University, 2005)
In early years of the European Community, there was considerable concern that the enforcement of trade marks could be used as barriers to trade between Member States. Thus, in the 1960s, the European Commission began work on the establishment of a Community Trade Mark. Such a trade mark was to be supranational and to provide territorial protection in all Member States of the European Community. The main subject of this study is based on the European Council Regulation (EC) No.40/ 94 of 20 December 1993 on the Community Trade Mark and the two Implementing Regulations (EC) No.2868/ 95 ('Regulation 2868/ 95', the 'Implementing Regulation', or the 'IR') dated 13 December 1995and (EC) No. 2869/ 95 dated 13 December 1995 on the fees payable to the Office for Harmonization in the Internal Market. In this study the focus in Part One is on how to create a Community Trade Mark, and thus describes the rules which are relevant to any Community Trade Mark application, and which must be complied with if a Community Trade Mark is to be registered. After being registered, the Community Trade Mark has to be protected by the legal system; thus, in Part Two an effort is made to show which protections apply to a Community Trade Mark. The ultimate aim in this study is to show that the creation of a CTM is beneficial both for businesses, and for the further unification and development of the Single Market of the European Union. I also has the capacity to enhance the trade relations of the EU with the rest of the world.

Avrupa Topluluğunun ilk yıllarında, ticari markaların uygulanmasının Üye Devletler arasındaki ticarete sınırlar getireceği konusunda önemli endişeler vardı. Bu sebeple, 1960'lı yıllarda Avrupa Komisyonu Topluluk Ticari Markasının kurulması için çalışmalara başladı. Böyle bir ticari markanın uluslarüstü bir gücü olması ve Avrupa Topluluğuna üye tüm devletler bakımından bölgesel bir koruma getirmesi gereklidir. Bu çalışmanın temel konusu Avrupa Konseyinin (EC) No.40/ 94 sayılı ve 20 Aralık 1993 tarihli Topluluk Ticari Markası Yönergesi ve 13 Aralık 1995 tarihli (EC) No.2868/ 95 ('Tamamlayıcı Yönerge' ya da 'TY') ve (EC) No. 2869/ 95 sayılı İç Pazarın Harmonizasyonu Ofisine ödenecek ücretlerle ilgili tamamlayıcı düzenlemelere dayanmaktadır. Bu çalışmanın Birinci Kısmında Topluluk Ticari Markasının nasıl yaratıldığı, ve bu sebeple Topluluk Ticari Markasına başvuruda uygulanan kurallar, ve Topluluk Ticari Markasının tescil edilmesinde uygulanan kurallar açıklanmıştır. Tescil edildikten sonra, Topluluk Ticari Markasının hukuki sistem tarafından korunması gereklidir; bu sebeple İkinci Kısımda Topluluk Ticari Markasının korumasında uygulanan koruma yolları anlatılmaya çalışılmıştır. Çalışmadaki nihai hedef, Topluluk Ticari Markasının hem ticari işletmeler açısından hem de Avrupa Birliği'nin Tek Pazarının işlerliğini ve gelişimini sağlamak bakımından arzettiği önemi vurgulamaktır.Topluluk Ticari Markası ayrıca Avrupa Birliği'nin dış dünya ile yürüttüğü ticari ilişkilerini de pekiştirecek yönde bir değer oluşturmaktadır.
Keywords: Avrupa Birliği; Avrupa Birliği Ticari Markası; Ticari Marka